Drying of the Aral Sea and changes in the landscape of the Aral Sea region (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the changes in the landscape of the Aral Sea region due to the drying up of the Aral Sea. It also provides information on the causes of landscape changes in the Aral Sea region and the flora and fauna of the landscapes. The article also provides information on the landscape of the Aral Sea region before the drying up of the Aral Sea. The article is based on a comparison of data from different databases and books, as well as feedback from the authors of the article on landscape change.